Peran Komunikasi Lintas Budaya Dalam Meningkatkan Kualitas Pendidikan - Aswaruddin, Aswaruddin; Ray, Aina Ul Mardiyah; Hasibuan, Irma Tussa’diyah; Diastami, Sylvi Marsella (Penerbit Widina, Widina Media Utama, 2025)
Cross-cultural communication is an important element in organizations operating in a global and multicultural environment. This research examines the role of cross-cultural communication in improving the quality of education. This research uses the Library Research method with a qualitative approach to study cross-cultural communication in improving the quality of education. The results of the analysis show that effective intercultural communication increases cultural awareness and appreciation, improves teacher-student relationships, and increases motivation and learning achievement. Cross-cultural communication strategies such as the use of inclusive language, nonverbal awareness, and respect for cultural differences are essential in creating a positive and inclusive learning environment.ABSTRAKKomunikasi lintas budaya merupakan elemen penting dalam organisasi yang beroperasi di lingkungan global dan multikultural. Penelitian ini mengkaji peran komunikasi lintas budaya dalam meningkatkan kualitas pendidikan. Penelitian ini menggunakan metode Library Research dengan pendekatan kualitatif untuk mengkaji komunikasi lintas budaya dalam meningkatkan kualitas pendidikan. Hasil analisis menunjukkan bahwa komunikasi efektif antarbudaya meningkatkan kesadaran dan penghargaan budaya, memperbaiki hubungan guru-siswa, serta meningkatkan motivasi dan prestasi belajar. Strategi komunikasi lintas budaya seperti penggunaan bahasa inklusif, kesadaran nonverbal, dan penghormatan perbedaan budaya sangat penting dalam menciptakan lingkungan belajar yang positif dan inklusif.